Focus on Reading : A handbook for teachers' - Hood, Sue.; Solomon, Nicky (Australia : National Curriculum Resource Centre, 1985)
This a handbook for learners to encourage the development of reading strategies in language teaching.
Keywords: English language; Reading skills; Focus on reading; English language -- Reading -- Study and teaching; English language -- Reading